Significance of Increased Rapid Treatment from HIV Diagnosis to the First Antiretroviral Therapy in the Recent 20 Years and Its Implications: the Korea HIV/AIDS Cohort Study - Kim, Yoon-Jung; Kim, Shin-Woo; Kwon, Ki Tae; Chang, Hyun-Ha; Kim, Sang Il; Kim, Youn Jeong; Kim, Min Ja; Choi, Jun Yong; Kim, Hyo Youl; Kim, June Myung; Choi, Bo Youl; Park, Bo Young; et al. (Journal of Korean medical science, 2019)
From December 2006 to December 2016, 1,429 patients enrolled in the Korea human immunodeficiency virus/acquired immune deficiency syndrome (HIV/AIDS) Cohort Study were investigated. Based on the year of diagnosis, the time interval between HIV diagnosis and initiation of antiretroviral therapy (ART) was analyzed by dividing it into 2 years. The more recent the diagnosis, the more likely rapid treatment was initiated ( < 0.001) and the proportion of patients starting ART on the same day of HIV diagnosis was increased in 2016 (6.5%) compared to that in 2006 (1.7%). No significant difference in the median values of CD4+ cell counts according to the diagnosis year was observed. In the past 20 years, the time from the HIV diagnosis to the initiation of ART was significantly reduced. Rapid treatment was being implemented at the HIV diagnosis, regardless of CD4+ cell count. Considering the perspective "treatment is prevention," access to more rapid treatment is necessary at the time of HIV diagnosis.